The Influence of Human Capital on Financial Performance and Corporate Value - MULYANINGTYAS MULYANINGTYAS (Jurnal GeoEkonomi, 2019)
Human Capital (HC) reflects the knowledge capital of employees of an organization. In this era there was a huge changes in the economic field where human capital would be a factor of production that has a vital role. One way to increase human capital for companies is to increase expertise through learning experience programs. Profitability is a reflection of the financial performance of a company and a company that is well aware of the management of Human Capital, because the good and bad of Human Capital will affect the company's financial position directly and affect the company's profitability in the end. This study aims to determine whether the influence of human capital on firm value with financial performance as an intervening variable in the banking companies on the IDX registered in 2012-2016. This study uses two approaches, namely descriptive approach and explanatory approach. The technique of determining the sample of this study was purposive sampling carried out on banking companies which during 2012 to 2016 were listed on the Indonesia Stock Exchange.